Multi-Scale Exploration of Convex Functions and Bandit Convex Optimization - Bubeck, Sébastien; Eldan, Ronen (arXiv:1507.06580v1 [math.MG], 2015)
We construct a new map from a convex function to a distribution on its domain, with the property that this distribution is a multi-scale exploration of the function. We use this map to solve a decade-old open problem in adversarial bandit convex optimization by showing that the minimax regret for this problem is O (poly(n)T√) , where n is the dimension and T the number of rounds. This bound is obtained by studying the dual Bayesian maximin regret via the information ratio analysis of Russo and Van Roy, and then using the multi-scale exploration to solve the Bayesian problem.
Best Paper Award